Occupational Stress in Intensive Care Units Nurses: A Cross-sectional Study - Mahya Torkaman; Naval Heydari; Maryam Kamali; Mohammad hosein Fadaei (Zanjan University of Medical Sciences and Health Services, 2019)
Abstract   Background: Occupational stress can have seriously negative effects on the physical, psychological, and economic dimensions of nurses working in the intensive care units (ICUs). Objectives: Thus, this study was conducted to determine occupational stress in nurses who work in ICUs. Methods: This cross-sectional study was carried out on 120 nurses in three hospitals in Kerman, southeastern Iran. Data were gathered by Socio-Demographic Information and Osipow Occupational Stress questionnaires. Results: The mean of occupational stress and all its constructs were at the moderate-high level. The highest mean score was related to role overload (37.11±3.63) while the lowest mean score belonged to role boundary (30.32±3.66). No statistically significant differences were found between the mean of occupational stress and participants' characteristics. Conclusion: Considering the moderate-high level of occupational stress in ICU nurses, we recommend hospital authorities to take appropriate measures to prevent and manage stressors in ICU nurses to improve the quality of care and patients' satisfaction